Features of styrene heterogegeous polymerisation under statistic conditions in the presence of emusifiers and co-surfactants - S. V. Zhachenkov; I. A. Gritskova; S. M. Levachev; M Khaddazh (Тонкие химические технологии)
The kinetics of styrene microemulsion formation in the presence of cetyl alcohol, n-dodecylmercaptan (n-DDM), and mixtures of both substances under conditions close to the emulsion polymerization was investigated. It was shown that cetyl alcohol and dodecylmercaptan differently influence under similar conditions on the intensity of the microdroplet creation on the phase boundary and on the rate of polymerization. It was shown that the concentration of n-DDM in the place of the polymerization corresponds to its value in the polymerization recipe only in the case of presence of more surface-active emulsifiers than n-DDM.